Two-Color Image Analysis Discriminates between Mineralized and Unmineralized Bone Nodules In Vitro - Kelly A. Purpura; Jane E. Aubin; Peter W. Zandstra (BioTechniques)
Functional assays of progenitor cell capacity for colony formation in vitro typically depend on the investigator's expertise with quantification. The ability to enumerate and analyze colony types with standardized criteria with no bias would be a useful tool for research and drug development. We report the development of a two-color automated analysis system for colony-forming unit-osteoblasts that is capable of reporting progenitor frequency and bone nodule number, size, and type (mineralized or unmineralized). Our image analysis system was validated using the rat calvaria cell model to measure in vitro bone nodule development. With computer-aided image analysis, data on nodules can be rapidly generated with a minimum of user bias and fatigue. This novel tool will distinguish mineralized and unmineralized bone nodules, facilitate quantification, enable large-scale experimental design, allow for long-term data storage and tracking, and lead to the identification of new parameters that impact bone development.